AT LEVE MED VOLD: Om seksualitet og vold blandt unge i Cape Town - Henriksen, Ann-Karina; Lindegaard, Marie Rosenkrantz (Tidsskriftet Antropologi, 2002)
The focus of the article is upon the relation between gender and violence as an aspect of everyday practice. It is suggested that strategies for living with violence inform gender perceptions. The article is based on research in Cape Town, South Africa and consentrates on how adolescents there speak about violence and strategies for safety. South Africa is renowned for high levels of violence such as rape or death by gunfire. Rather than focus on these violent acts from the perspective of either the victim or perpetrator, the focus lies in the implications for the witnesses, who live with the threat of violence in their daily lives. Narratives related to violence and strategies for safety show how violence manifests itself. The authors argue that women and men are discursively informed to respond to and perceive violence differently. Men are agents of violence as protectors and perpetrators, and women are pacified and potential victims. Furthermore the study emphasises that violence maintains patriarchal gender roles and thereby becomes a major barrier to rethinking gender perceptions and gender equality.